Sistema de indicadores de sustentabilidade empresarial: uma aplicação no setor sucroenergético da zona da mata paraibana - Moreira, Josicleide de Amorim Pereira (2020)
The Corporate Sustainability Indicator Systems appear as instruments that identify the advances towards sustainable development. In this sense, this work has the general objective of conceiving, based on the Corporate Sustainability Grid, a system of indicators that encompasses the economic, environmental, social and cultural dimensions, in order to identify the sustainability level of a sugarcane bioelectricity sector company in the Zona da Mata in Paraiba. With this purpose, three articles were accomplished: the first sought to identify the Corporate Sustainability Indicator Systems with specific use in the sugarcane bioelectricity sector. The research is classified as exploratory and descriptive, with quantitative and bibliometric approach. The Social Network Analysis was chosen, specifically, regarding the centrality degree between the actors of the analyzed network. The results point to the insufficiency of scientific productions about Corporate Sustainability Indicator Systems, having identified only one work directed to sugarcane bioelectricity sector within the research criteria. The second article aims to present the potentialities arising from the generation expansion of the sugarcane bioelectricity in Paraíba in alignment with the perspectives of sustainable development. The research is characterized as exploratory, with quantitative approach. The study area covered the Zona da Mata in Paraíba. To measure the generation potential of the sugarcane bioelectricity, a calculation methodology was used, based on scenarios proposed by Perdoná, in 2015, considering the volume of sugarcane processed in the 2018/19 harvest. In addition, na estimate of annual gross revenue was measured, which could be obtained from the sale of this generated bioelectricity, if it were sold at the 004/2019 Auction. The results show that adopting the scenario consisting of a 100 bar / 540 ° C boiler, a fluidized bed and a regenerative cycle, the Paraíba sugarcane bioelectricity sector would have generated bioelectricity equivalent to 660.47 GWh, and if it had been negotiated at the 004 / 2019 Auction, the sector would have invoiced the equivalent to R$ 124.3 million in gross revenue per year. It is noteworthy to point out that the expansion of the sugarcane bioelectricity for the State provides potentialities aligned with the prospects of sustainable development. Finally, in the third article, a proposal for a Corporate Sustainability Indicator System is presented. It integrated the economic, social, environmental and cultural dimensions, based on the Corporate Sustainability Grid, with applicability to the sugarcane bioelectricity sector of the Zona da Mata in Paraíba. The research is classified as exploratory and descriptive, with quantitative approach. For the system design, it was decided to consult specialists and social actors, by means of the use of a form that served to determine the scores that make it possible to identify the sustainability level of the analyzed company. The research spatial limit includes the Zona da Mata in Paraíba, and the sample is classified by convenience. For the fulfillment of the system, a form with applicability in the plant participating in the research was chosen as data collection. Taking into account the results, the imminently partial satisfactory Scores of Sustainability for the economic dimension, satisfactory scores for the social and environmental dimensions and imminently unsatisfactory for the cultural dimension were identified. In addition, it was possible to identify the Corporate Sustainability Score as imminently satisfactory sustainability, with the analyzed plant being positioned in the Corporate Sustainability Grid in the 27th position